Systemic regulation of vascular NAD(P)H oxidase activity and nox isoform expression in human arteries and veins. - Guzik, T; Sadowski, J; Kapelak, B; Jopek, A; Rudzinski, P; Pillai, R; Korbut, R; Channon, K (2004)
OBJECTIVE: Impaired endothelial function, characterized by nitric oxide scavenging by increased superoxide production, is a hallmark of vascular disease states. However, molecular mechanisms regulating superoxide production in human blood vessels remain poorly defined. METHODS AND RESULTS: We compared endothelial function, vascular superoxide production, and the expression of NAD(P)H oxidase subunits in arteries and veins from patients undergoing coronary bypass surgery (n=86). Superoxide release was similar in arteries and veins. Inhibitor studies revealed that the NAD(P)H oxidase system was a quantitatively and proportionately greater source of superoxide in veins, whereas xanthine oxidase also contributed significantly to superoxide production in arteries. Moreover, NAD(P)H oxidase molecular composition differed in veins and arteries; veins expressed more nox2 and p22phox, whereas the relative expression of nox4 was greater in arteries. However, there were strong correlations between p22phox and nox4 expression and between superoxide production, NAD(P)H oxidase activity, and endothelial function in arteries and veins from the same patient. CONCLUSIONS: In individuals with coronary artery disease, changes in vascular superoxide production, endothelial function, and NAD(P)H oxidase activity and expression are related in veins and arteries. These findings highlight the importance of systemic effects on the molecular regulation of the NAD(P)H oxidases in human vascular disease. Endothelial dysfunction is characterized by increased superoxide production. NAD(P)H oxidase activity and endothelial function are correlated in veins and arteries in coronary artery disease, suggesting regulation by systemic factors. The expression of the NAD(P)H oxidase subunits p22phox and nox4, although different in veins and arteries, are also correlated.